Pengaruh Kualitas Layanan, Harga, Dan Citra Merek Terhadap Kepuasan Konsumen Handphone di Karesidenan Surakarta - Ahmad Sidiq; Kasidin Kasidin (Riset Manajemen dan Akuntansi, 2021)
This study aims to find out how Service Quality, Price, Brand Image have an effect and are significant either partially or simultaneously (simultaneously) on Mobile Consumer Satisfaction in the Residency of Surakarta. With multiple linear regression analysis to test the hypothesis with t-test and F test with a sample of 109 respondents with purposive sampling technique, then obtained the partial test, namely t-count service quality of 4,588 sig 0.00, t-test for Price of 3.421 sig 0.001, t-test for Brand Image of 3.930 sig 0.000 each compared to t-table of 1.984 and Model Test with Fount test of 71.679 with sig 0.000 and F-table 2.70. Service Quality, Price, Brand Image have an effect and are significant either partially or simultaneously (simultaneously) on Mobile Phone Consumer Satisfaction in Surakarta Residency. Suggestion For mobile phone companies should maintain the three factors that influence consumer satisfaction, namely price, service quality, and brand image because it has contributed to the influence of 67.2%. And the management of the mobile phone company should improve the quality of service because based on the survey the price is still in the medium category